(untitled) (Journal of Computational Mathematics, 2000)
In this paper parallel Rosenbrock methods in real-time simulation are presented on parallel computers. Their construction, their convergence and their numerical stability are studied, and the numerical simulation experiments are conducted on a personal computer and a parallel computer respectively.